IRON, COPPER AND MOLYBDENUM IN THE DIFFERENT BODY PARTS O F SOME CLUPEOIDS - Rao, T Appa (Indian Journal of Fisheries, 2011)
The amounts of ifon, copper and molybdenum in the different tissues of eight species of clupeoids belonging to the genera Stolephonis, Thryssa and Sardinella were determined. Irt all the species, the concentration of each element did not bear any relation to Mze. It was observed that iron and copper were concentrated more in heart and liver than in stomach, pyloric caecae, kidneys, ovaries, testes, flesh and bone.